Collective Action and Women's Agency : A Background Paper - Evans, Alison; Nambiar, Divya (World Bank, Washington, DC, 2014)
Following the findings and policy messages of the World Development Report (WDR) on gender equality and development 2012, the World Bankapos;s gender and development group are seeking to deepen the evidence base on promoting womenapos;s agency as a basis for enhanced action on gender equality. A component of this work is a review of evidence on the relationship between collective action and womenapos;s agency: whether and how different forms of collective action enhance womenapos;s ability to exercise agency in key domains and the operational implications for Bank policies and programs. The paper seeks to clarify the conceptual terrain of collective action; identify the links with womenapos;s agency; and draw lessons from the evidence on what works and what does not for boosting development and gender-equality outcomes. It draws attention on the somewhat smaller body of empirical research examining the mechanics of collective action and its links with economic and social wellbeing, particularly within developing societies. The findings are complex, but the overall conclusions are consistent with an emerging body of literature now questioning participation as a silver bullet in development and calling for more flexible, context-sensitive approaches for promoting agency, and empowerment.